BAKPAO HANJELI SEBAGAI ALTERNATIF KUDAPAN SEHAT - Nani Ratnaningsih, Febrian Taofik Romandon (Prosiding Pendidikan Teknik Boga Busana, 2020)
The consumpttion of wheat flour in Indonesia is needed for an alternative with using local cereal such as hanjeli (Coix lachryma-jobi L.). The goals of this reaserch are to find out the bakpao accepted (chinese bun) formula, nutrition value information, and acceptence rate of bakpao hanjeli. This reaserch uses Reaserch and Development Methode and 4D appoarchment which are define, at this level the deteremination of standar recipe was carried out and the proccesses of hanjeli flour was took place. Dessign, at this level substitution of hanejli flour was determined. Develope, at this level bakpao hanjeli was developed by creating the filling and validation testing was carrried out. Dessiminate, at this level we did restrcted scale teting by 30 people semi trained panelists and 80 people unttrained panelist. The accpeted formula of bakpao hanjeli is recipie with 30% substitutions of hanjeli flour, the accpetance rate of bakpao hanjeli on semi trained and untrained panelists shows that bakpao hanjeli is accpeted well. Control and developed variables are not different seginificantly. Key Word : Hanjeli, Chinese buns, snacks